Pengaruh Ekuitas Merek dan Relational Terhadap Loyalitas Konsumen pada Supermarket Kaisar Siantan - Magisa, Nurul Septya; Hardayu, Audisty Prana (Journal of Economic and Management (JECMA), 2023)
This study aims to determine and analyze the effect of brand and relational equity on consumer loyalty in Kaisar Siantan Supermarket. Data collection in this study was collected by means of observation and questionnaires (online and offline). The population in this study are consumers or members who shop at Emperor Siantan with a total of 50 consumers and members in 2022. The sampling technique used in this study is to use the Saturated Sampling Technique, which is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small, less than 50 people, or research that wants to make generalizations with very small errors. Another term for a saturated sample is a census, where all members of the population are sampled. Data analysis used normality test, multiple linear regression analysis, t test, v test. Data analysis was carried out using the IBM SPSS Statistics 25 application. The results of this study showed that brand equity X1 and relational X2 had a positive impact on consumer loyalty in Kaisar Siantan Supermarket. Keyword: Brand Equity, Relational, Consumer Loyalty